Analysis the different of knowledge and history consumed fastfood junk food between mother breast cancer first stadium and last stadium at RSUD Dr Kanudjoso Djatiwibowo Balikpapan 2016 - Sri Hazanah; Rus Andraini (Humanistic Network for Science and Technology (HNST), 2020)
Breast cancer is a malignant and deadly disease for women. The high number deaths causes by breast cancer comes second after cerucal cancer, some of the risk factors of breast cancer are fast food or junk food and the lack of knowledge of the symptoms. The purpose of this study was to analyze the different of knowledge and history consumed fast food junk food between mother breast cancer first stadium and last stadium at Dr Kanudjoso Djatiwibowo Hospital, Balikpapan. The approach of this research was restrospective. The respondents consisted of 45 people individuals by using accidental sample technique. The data were obtained using questionniare, then analyzed using Chi square test and logistic regression test. The result with minimum knowledge were 25 (55.6%), who consumed fast food were 34 (75.6%), also there was a correlation between knowledge and breast cancer with p-value of 0.006. Based on the regression test, there was correlation between knowledge and breast cancer, with p-value of 0.04; while the p-value of the correlation between fast food and breast cancer was 0.264. The conclusion that the dominant factors of breast cancer was knowledge. There fore, health professionals, the agencies to give a socialization, giving information about breast health, to consume healthy food for our body as prevention of breast cancer. Keywords: knowledge; breast cancer